The Learning Process with Contextual Approach to Improve Students' Motivation and Mathematics Learning Achievement - Triyanto, Aris; Istiqomah, Istiqomah; Arigiyati, Tri Astuti (Journal of Instructional Mathematics, 2022)
The aim of this study was to describe the learning process with a contextual approach to improve motivation and Mathematics learning achievement on Integer topic for seventh grade students of State Junior High School 1 Bonggo in the 2019/2020 academic year. This research was conducted in the seventh grade of State Junior High School 1 Bonggo, Sarmi Regency, Papua Province. The Classroom Action Research (CAR) was used as the research method. The research object involved the whole process of implementing Mathematics learning with a contextual approach to improve motivation and Mathematics learning achievement of seventh grade students of State Junior High School 1 Bonggo, Sarmi Regency, Papua Province. Based on the research results, the Mathematics score of pre-cycle to cycle I improved from 50.4 to 67.2, in cycle II it improved further to 79.4. Meanwhile, the motivation in Mathematics learning obtained pre-cycle score of 65.8, cycle I score of 70, and cycle II score of 91. It is advised that teachers should use the CTL learning method on other subjects to improve students' motivation and Mathematics learning achievement.